2021
DOI: 10.1108/ijshe-01-2021-0014
|View full text |Cite
|
Sign up to set email alerts
|

Transformational learning for sustainability leadership – essential components in synergy

Abstract: Purpose Transformative learning (TL) and leadership are key leverage points for supporting society’s transition toward sustainability. The purpose of this study is to identify essential components of TL within an international sustainability leadership master’s program in Sweden that has been described by many students as life-changing, empowering and transformational. Design/methodology/approach Alumni spanning 15 cohorts provided answers to a survey and the responses were used to map components of TL as ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Many studies reveal the effectiveness of transformative learning in preparing future leaders, one of which is a study conducted by Bryant et al which identified the essential components of transformative learning that are life-changing, empowering, and transformational in the student's life. The study suggested the essential components that support transformational change according to many respondents (Bryant et al, 2021). This study indeed gives a fresh direction among the researcher and practitioners to retain the essential components in developing a transformative learning model.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…Many studies reveal the effectiveness of transformative learning in preparing future leaders, one of which is a study conducted by Bryant et al which identified the essential components of transformative learning that are life-changing, empowering, and transformational in the student's life. The study suggested the essential components that support transformational change according to many respondents (Bryant et al, 2021). This study indeed gives a fresh direction among the researcher and practitioners to retain the essential components in developing a transformative learning model.…”
Section: Introductionmentioning
confidence: 72%
“…This study tries to make the comprehensive yet compact component from the instructional design point of view of transformative learning instructional systems. We enrich the previous studies that identify the transformative learning component only from a partial point of view in transformative learning (Bryant et al, 2021;Foshee et al, 2017;Kitchenham, 2008;Mezirow et al, 1997;Moon, 2011;Sawatsky et al, 2018;Schnepfleitner & Ferreira, 2021). We can mention a study such as a study conducted by Bryant et al (2021) which identified the essential components that support transformational change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is one of the oldest sustainability leadership master’s programs and Trencher et al (2018) identified it as one of 14 best practice programs worthy of study globally. In addition, a previous study found that 91.7% of alumni surveyed stated that the program was transformational for them and identified the essential components that have created the transformational experience for many of the students (Bryant et al , 2021). The alumni operate across a range of sustainability-related disciplines and vocations, and their roles range from corporate sustainability positions to facilitation, consultation and educational work that consider social and ecological sustainability contexts.…”
Section: Methodsmentioning
confidence: 99%
“…The development of contemplative and reflective pedagogies has been suggested as an option that promotes Intrapersonal development, (Ayers et al 2020;Eaton et al 2016;Wamsler 2020) as have transformational learning environments that seek to promote active disorientation with reflection to promote self-knowledge (Bryant et al 2021;Mezirow 1997). Furthermore, pedagogies encouraging hope, purpose, love, and peace in a time of socio-ecological crisis have connected sustainability and spirituality and gained acceptance as increasingly important to sustainability practice (Fry and Egel 2021;Ojala 2017).…”
Section: The Intrapersonal As Integral To Sustainability Practicementioning
confidence: 99%